Portable Arduino® platform for electrochemical sensors - Ithnin, Mohamad Hafiz; Arris, Farrah Aida; Wan Salim, Wan Wardatul Amani (IIUM, 2016)
Quantifying water-quality parameters in the field demands a portable device capable of performing precision measurements on a minimal sample. The one-device-fits-all concept is useful for environmental monitoring of multiple water-quality parameters. Current commercial and portable devices on the market for water-quality measurements measure a single parameter, are bulky in size, and are relatively expensive. In this project, we design and assemble a portable sensor platform utilizing an Arduino®-based microcontroller that has the capability to interface with commercial/customized electrochemical sensors. The project envisions a portable multiplex device that can perform highly sensitive and rapid in-situ measurements of water-quality parameters, using an Atlas ScientificTM printed circuit board (PCB) for pH and dissolved oxygen (DO). The PCB connects to the Arduino® microcontroller using a multi-circuit connection to interface with each electrochemical sensor. This project covers all methods in developing a multi-parameter portable device for water-quality measurement, one that can be upgraded to measure other analytes, owing to the flexibility of the Arduino®-based open-source microcontroller.